An innovative environmental process for the treatment of scrap Nd-Fe-B magnets. (1st November 2020) - Kumari, Archana; Jha, Manis Kumar; Pathak, Devendra Deo
Abstract: Strict environmental regulations as well as requirement of conservation of natural resources compelled the researchers to recycle the metal values from secondary resources. The scrap magnets found to be a potential alternative resource to extract rare earth metal, Nd. Present paper reports a novel process flow-sheet for the recycling of scrap Nd-Fe-B magnets to recover Nd as marketable salt and other valuable by-products. The Nd-Fe-B magnets were demagnetized, crushed and charged to atmospheric leaching resulting in ~99.99% recovery of REMs (Nd, Pr, Dy) and Fe using 1 M H2 SO4 solution at room temperature for 90 min and pulp density 50 g/L. The obtained leach liquor was subjected to acid extraction procedure by mixing the liquor with 70% TEHA diluted in kerosene for 10 min, which requires five stages for complete extraction of acid from the liquor having O/A ratio 2:1. Ammonia solution was used to increase the pH of acid free leach liquor to 1.65 for the precipitation of Nd (with minor amount of Pr and Dy) and above that to precipitate Fe. Further, processing of these valuables make them industrially applicable. The leached residue was checked using Toxicity Characteristics Leachability Procedure (TCLP) test and found the remained metals within the permissible limit. This process offers a simple and efficient means to reduce the toxicological effect by recovering Nd from magnets of computer hard disks. Highlights: A novel process flow-sheet for the recycling of Nd-Fe-B magnets was proposed. Reports atmospheric leaching followed by selective precipitation of Nd salt. Marketable salt of Nd of purity ~98% was produced. Red oxide was produced as marketable by-product. Conservation of natural resources as well as mitigation of pollution.